Effectiveness of REACT Learning Based on Inquiry Learning Toward Students Critical Thinking Skills - Irma Rahmawati; Abdullah Ardi; Ranat Mulia Pardede; Muh.Safar; Novianty Djafri; Suyahman (AKADEMI TEKNIK ADI KARYA, 2024)
This research aims to determine the effect of inquiry learning-based REACT learning to improve students' critical thinking skills. This research is a type of quantitative research with a meta-analysis approach. The data source comes from an analysis of 14 national and international journals published in 2020-2023. Data search process by searching the Google Scholar, ScienceDirect, ERIC and IEEE databases. Data collection techniques are direct observation and documentation. Data selection uses the PRISMA method which consists of identification, screening, eligibility and inclusion. Data analysis by calculating the effect size value from each relevant study with the help of JSAP software. The research results show that there is a positive influence of inquiry learning-based REACT learning on students' critical thinking skills with an average effect size value (ES = 0.872) in the high category. The findings explain that REACT learning based on inquiry learning is effective for improving students' critical thinking skills at school.